Scalable and efficient authentication scheme for secure smart grid communication. Issue 4 (1st July 2020) - Hammami, Hamza; Ben Yahia, Sadok; Obaidat, Mohammad S.
Abstract : Smart grids represent the latest trend that has disrupted the energy supplier sector. They are in the form of smart meters that automatically communicate power consumption data to the power grid operator. In fact, the smart‐grid technology is a great solution for energy suppliers and their end customers, enabling them to perform more frequent measurements of energy, monitor their consumption and thus control the amount of their energy bills. Although the smart‐grid technology brings significant gains in performance and economy to its users. However, this advanced technology immediately raises different types of attacks that can adversely affect the operation of smart grids by falsifying electricity consumption data transmitted between smart meters and the power distribution server and therefore through the generation of incorrect energy billing invoices. The reflection carried out in the proposed approach is part of this problem. It is particularly concerned with realising a new privacy‐protected authenticated key agreement scheme for secure communication between smart meters and energy providers. The conducted experiments show that the proposed authentication scheme exceeds its competitors in terms of calculation costs and resistance to various types of attacks.